The Four Opens: Open Source Beyond the Code. - Vancsa, Ildiko; Riehle, Dirk (Computer (00189162), 2022)
This article describes a set of guiding principles that open infrastructure communities, such as OpenStack, use to create and maintain balanced ecosystems around projects and navigate the challenges and intricacies of open collaboration.